Real or fictional? Digital entrepreneurial narratives and the acquisition of attentional resources in social entrepreneurship - Chenfang Zhao; Zhiyang Liu; Chao Zhang (Journal of Innovation & Knowledge (JIK), 2023)
Digital entrepreneurial narratives compensate for the limited interactivity of traditional entrepreneurship narratives. This is achieved by incorporating elements of social entrepreneurship into tangible, real or fictional scenarios, thereby providing immersive experiences for the audience. In this sense, social entrepreneurs construct shared meanings and form socially identifiable values through the joint participation, communication, and value creation of entrepreneurs and audiences. We conceptualized the digital entrepreneurial narrative and proposed documentary and fictional narratives as its most salient features. Then, we explored the effect of these narratives on attentional resources in a digital entrepreneurial narrative from the perspective of sensemaking theory. Based on novel methods of natural language processing and machine learning, the empirical results from an examination of 304 social entrepreneurs who participated in the short-video platforms indicated that both documentary and fictional narratives have a positive impact on the acquisition of attentional resources for social entrepreneurship. Additionally, we found the documentary aspect of digital entrepreneurial narratives attracts attentional resources by fostering a shared sense of meaningfulness. However, the mediating effect is less effective with fictional narratives. Our results broaden the study of entrepreneurial narratives, and also expand the content of social entrepreneurial legitimacy and sensemaking perspectives.
Keywords: L26; L31; O40; Q01; E71; 650; Attentional resources; Digital entrepreneurial narrative; Sensemaking; Social entrepreneurship